Effects of purified exosome product on rotator cuff tendon-bone healing in vitro and in vivo. (September 2021) - Ren, Ye; Zhang, Shuwei; Wang, Yicun; Jacobson, Daniel S.; Reisdorf, Ramona L.; Kuroiwa, Tomoyuki; Behfar, Atta; Moran, Steven L.; Steinmann, Scott P.; Zhao, Chunfeng
Abstract: Exosomes have multiple therapeutic targets, but the effects on healing rotator cuff tear (RCT) remain unclear. As a circulating exosome, purified exosome product (PEP) has the potential to lead to biomechanical improvement in RCT. Here, we have established a simple and efficient approach that identifies the function and underlying mechanisms of PEP on cell-cell interaction using a co-culture model in vitro. In the in vivo trial, adult female Sprague-Dawley rats underwent unilateral surgery to transect and repair the supraspinatus tendon to its insertion site with or without PEP. PEP promoted the migration and confluence of osteoblast cells and tenocytes, especially during direct cell-cell contact. Expression of potential genes for RCT in vitro and in vivo models were consistent with biomechanical tests and semiquantitative histologic scores, indicating accelerated strength and healing of the RC in response to PEP. Our observations suggest that circulating exosomes provide an effective option to improve the healing speed of RCT after surgical repair. The regeneration of enthesis following PEP treatment appears to be related to a mutually reinforcing relationship between direct cell-cell contact and PEP activity, suggesting a dual approach to the healing process.